PERLUASAN THEORY OF PLANNED BEHAVIOR DALAM MENJELASKAN FAKTOR-FAKTOR YANG MEMENGARUHI INTENSI MENERAPKAN PERILAKU HIDUP SEHAT PADA MASA COVID-19 - Luthfia Nur Alyssa; Ikhsan Fuady (Dian Nuswantoro Semarang, 2022)
The COVID-19 that has hit the world makes healthy living behavior very important to do as a preventive measure. In implementing a healthy lifestyle, there are several factors that influence the intention to do so. The main purpose of this study was to determine the effect of using Instagram to seek health information, subjective norms, behavioral control, and attitudes towards students' intentions in implementing healthy living behaviors. The theory used is the expansion of the Theory of Planned Behavior. The population of this study is active college students aged 18-24 years, domiciled on the island of Java, and have or are currently using Instagram. The total sample used is 121 people. Data was collected through the distribution of online questionnaires. The results of the data were tested using descriptive statistical analysis and multiple linear regression. The results obtained show that the use of Instagram for health information and subjective norms partially has no effect on the intention of healthy living behavior. Another result is that partially attitude and behavioral control affect students' intentions to implement healthy lifestyle behaviors.